Forças de corte geradas por torneamento : um estudo de caso das ligas Cu-Al-Be e Cu-Al-Be-Nb-Ni passíveis do efeito memória de forma - Silva, Francisco Valdenor Pereira da (2014)
The shape memory alloy, more specifically constituted of CuAlBe, have played an important role in the manufacture of electromechanical components, especially when worked requests from thermal and/or applied stresses. At first, this present research work, were obtained, by casting the gas, samples of alloys Cu-11.8%Al-0.60%Be; Cu-11.8%Al-0.55%Be; Cu-11.8%Al-0.55%Be-0.50%Nb-0.27%Ni (wt%). Sequentially, quenched to half of them, with the intention of doing them acquire the shape memory effect. In a third moment, said samples passed assays DSCs, aiming raise the temperature curves of phase transformation (austenite: Ai/Af and martensite: Mi/Mf). The main study, performed during machining by turning dry, using a piezoelectric dynamometer, were defined the cutting forces of samples tempered and not tempered. In compliance with the track methodology, were applied five replicates, with four levels of cutting speed for each of the samples tested. The signals from the dynamometer were processed in LabVIEW and further processed in by a program done on MatLAB. Secondary assays were also performed soon after machining by turning dry. In the first, by means of a K-type thermocouple, temperatures of machining were measured along the stride; on the second, by assay of circularity, it was verified if there was or no retention of the martensite in the samples of shape memory alloys. It was found that the percentage of beryllium and nickel present in the alloys investigated, as well as the introduction of niobium as a grain refiner were decisive for achieving the results